PERAN WANITA DALAM PENGAMBILAN DAN EKSEKUSI KEPUTUSAN PENGELOLAAN KEBUN KELAPA SAWIT DI PROVINSI BENGKULU SERTA FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Diah Nursita; Ketut Sukiyono; Ellys Yuliarti; Nur Qomariah Hayati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
Oil palm plantations are the main source of income for farmers in Bengkulu Province, where women also play roles in decision-making and the implementation of plantation management decisions, although their roles are not yet fully recognized. This study aimed to analyze women’s roles in decision-making and decision execution in oil palm plantation management and to identify the factors influencing those roles. The research was conducted on 240 oil palm farming households in Mukomuko and Seluma Regencies using a survey method. Data were collected through interviews using questionnaires, observations, and documentation. The data were analyzed using descriptive quantitative analysis to describe patterns of women’s roles, while multinomial logistic regression analysis was employed to identify the factors affecting women’s roles in decision-making and decision execution. The results showed that the dominant pattern of decision-making was joint husband–wife decision-making at 37.19%, indicating that women’s roles in decision-making were at a moderate level. Meanwhile, in decision execution, the dominant pattern was husband-dominant at 38.54%, indicating that women’s roles in implementing decisions were still relatively low. Simultaneously, age, education level, farming experience, husband’s support, and gender norms significantly influenced women’s roles in decision-making and decision execution in oil palm plantation management.